ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL DITINJAU BERDASARKAN GENDER PADA MATERI GETARAN DI SMP - Anasari, Fitri; Tandililing, Edy; Syaiful, Syaiful (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the profile error and the difference in form errors in completing the matter of review of gender on the material vibration in SMP Negeri 1 Binjai Hulu. The method used in this research is descriptive method. The study sample were 32 students were taken using simple random sampling technique. Data collection tool in this research is test. From the analysis of data obtained by the profile error experienced by students that is the fault of the concept, systematic error and random error. The difference forms the error between the men with the percentage of on errors the concept of 32.5 %, a systematic error of 11.25 % and random errors 13,75 %. women with a percentage of that error the concept of 23,75 %, a systematic error of 11.25 % and random error of 11.25 %.Keywords: error analysis, Gender, vibrationÂ